STUDY OF PHYTOPLANKTON AS BIOINDICATORS OF ORGANIC MATTER POLLUTION LEVELS IN THE ESTUARY OF KENDARI BAY WATERS - Ali Said, Muhammad Dwi Fauzan; Kasim, Ma’ruf; Salwiyah, Salwiyah (Jurnal Ilmu Kelautan SPERMONDE, 2024)
The study aims to find out the structure of the phytoplankton community including abundance, dominance and to know the pollution of organic material in the Gulf of Kendari river stream using the sapropic index based on the phytoplankton as its indicator. The study was conducted from August to September 2022. The determination of the sampling station is carried out purposively by the sampler or sampler that has been planned by the researcher taking into account various considerations of conditions in the research area that may represent the conditions of the waters. The sampling technique was vertically carried out by tapping 150 L of seawater and then filtered using net plankton as many as 1 repetition at each station, then the sample filtered is inserted into a sample bottle and added preservatives. The samples are preserved using 3% formalin. The abundance calculation results of phytoplankton at each observation station during the study range between 269-2733 ind / l. The result of the calculation of the dominant index of each station during the study ranged from 0.17-0.96. The highest value was obtained at 0.17 and the lowest at 0.96. Measurement results of chemical physics parameters of water obtained temperature range 30-31 oC, current rate 0.09-0.37 m/second, TSS 0.3670-1.3395 mg/l, DO 5-6 mg/L, nitrate 0.134-0.163 mg / l, phosphate 0.60-0.285 mg /L.